On the interaction of speakers’ voice quality, ambient noise and task complexity with children’s listening comprehension and cognition - Lyberg-Åhlander, Viveka; Brännström, K. J.; Sahlén, Birgitta S. (Frontiers in Psychology, 2015)
Suboptimal listening conditions interfere with listeners’ on-line comprehension. A degraded source signal, noise that interferes with sound transmission and/or listeners’ cognitive or linguistic limitations are examples of adverse listening conditions. Few studies have explored the interaction of these factors in paediatric populations. Yet, they represent an increasing challenge in educational settings. We will in the following report on our research and address the effect of adverse listening conditions pertaining to speakers’ voices, background noise and children’s cognitive capacity on listening comprehension. Results from our studies clearly indicate that children risk underachieving both in formal assessments and in noisy class-rooms when an examiner or teacher speaks with a hoarse (dysphonic) voice. This seems particularly true when task complexity is low or when a child is approaching her/his limits of mastering a comprehension task.